2017
DOI: 10.1186/s12884-017-1463-9
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and determinants of pathways to reach comprehensive emergency obstetric and neonatal care (CEmONC) in South Sudan: qualitative diagrammatic pathway analysis

Abstract: BackgroundMaternity referral systems have been under-documented, under-researched, and under-theorised. Responsive emergency referral systems and appropriate transportation are cornerstones in the continuum of care and central to the complex health system. The pathways that women follow to reach Emergency Obstetric and Neonatal Care (EmONC) once a decision has been made to seek care have received relatively little attention. The aim of this research was to identify patterns and determinants of the pathways pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
66
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(69 citation statements)
references
References 42 publications
2
66
0
1
Order By: Relevance
“…In this sense, the use of the alert line alone to trigger referrals from peripheral to higher level hospitals may have unnecessarily increased referrals of women who otherwise had labours that were progressing normally. This may have had huge emotional, physical, and costs implications not only for the women, the fetus, and their families, but also for healthcare providers in referring and receiving facilities and the health system, in particular in places where referral systems are suboptimal or where higher level maternity units are overcrowded or understaffed …”
Section: Discussionmentioning
confidence: 99%
“…In this sense, the use of the alert line alone to trigger referrals from peripheral to higher level hospitals may have unnecessarily increased referrals of women who otherwise had labours that were progressing normally. This may have had huge emotional, physical, and costs implications not only for the women, the fetus, and their families, but also for healthcare providers in referring and receiving facilities and the health system, in particular in places where referral systems are suboptimal or where higher level maternity units are overcrowded or understaffed …”
Section: Discussionmentioning
confidence: 99%
“…Recently, a study of 119,244 pregnancies in the Brong Ahafo region of Ghana, found that facility delivery and shorter travel distance did not improve survival bene ts for women or newborns, unless births occurred in high quality or CEmOC facilities [25]. Others have shown similar results [26][27][28]. It is imperative that high risk obstetric patients reach the right facility, in a timely manner.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies, however, have described numerous barriers in accessing appropriate care beyond distance alone, including: delay in the recognition of a problem; needing to collect money for treatment or transport; waiting for relatives; needing permission; patient preferences for traditionalist and spiritual practices; refusal of referral due to fear of disrespectful care, medical procedures, or surgery; waiting for transport; and tra c congestion [1-3, 5, 6, 11, 22, 23, 26, 27, 29]. Also, in some cases, pregnant women are referred from one facility to another on the basis of no bed availability or lack of resources, until it is too late [28,29]. Fortunately, in the present report, this occurred for only 9 (1.4%) patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations